Logistic Regression Model for Assessing Factors Affecting Timeliness of Financial Statement Submission - Rumiyani, Eri Ayu; Resmi, Siti; Transistari, Ralina; Indarto, Muhammad Roni (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
Financial information is helpful if it fulfills fundamental characteristics. One of these characteristics is timeliness. This article aims to examine the elements that affect financial statement timeliness. This research is conducted on mining companies listed on the Indonesian stock exchange from 2016 to 2018. The data analyzed were panel data of 69 observations obtained from 23 companies over three years. The data was processed using Eviews9 and logit regression analysis techniques. The investigation demonstrates that the current ratio has a considerable favorable influence on the timeliness of financial statements for a variety of mining businesses listed on the Indonesian Stock Exchange (IDX) between 2016 and 2018. On the other hand, return on assets, and company size has no significant effect on the timeliness of financial statements. The implication of the results of this study is that better regulations are needed to improve public companies in submitting financial reports on time. Published financial statements are information for making informed decisions by interested users. Keywords : Current Ratio; Return on Asset; Company Size; Financial Statement; Logistic Regression Model.